Profiles of Depressive Symptoms and Anger in Men: Associations With Postpartum Family Functioning - Macdonald, Jacqui A.; Greenwood, Christopher J.; Francis, Lauren M.; Harrison, Tessa R.; Graeme, Liam G.; Youssef, George J.; Di Manno, Laura; Skouteris, Helen; Fletcher, Richard; Knight, Tess; Williams, Joanne; Milgrom, Jeannette; et al. (Frontiers in Psychiatry, 2020)
Background: Evidence suggests that men commonly experience depression as feelings of anger; yet, research has not investigated what this means for the manifestation of depressive symptoms in the early years of fatherhood and for key indicators of family functioning. Methods: Using data from a longitudinal cohort study of men at the normative age for entering fatherhood (28-32 years), we conducted latent class analyses to identify patterns of depressive symptoms and 3 sub-types of state anger (feeling; verbal; physical). We then assessed whether class membership was associated with paternity status (n=535). In a subsample of fathers of infants aged up to 18 months (n = 162), we prospectively assessed associations with paternal-infant bonding, co-parenting, perceived social support, paternal involvement in childcare and alcohol use up to two years later. Results: Five classes emerged that differentiated men by anger and depressive symptom severity and by the degree to which men endorsed the feeling of wanting to express anger physically. Compared to the reference class with minimal symptoms, fathers had a higher probability of being in either the mild or most severe symptom classes. Fathers in symptomatic classes were at higher risk of lower levels of social support, co-parenting problems, and paternal-infant bonds. Class membership was not associated with alcohol use or paternal involvement in childcare. Conclusions: Our results reveal patterns of co-existing symptoms of depression and anger in fathers of infants that will be relevant to men’s own need for support, their family safety, partner mental health and child developmental outcomes.